Introduction to Light Properties and Basic Principles of Spectroscopy at the High-School Level: A Pilot Study - Maria Antonietta Carpentieri; Gioia Fano; Sandro Jurinovich; Valentina Domenici (MDPI AG, 2023)
Spectroscopy is the basis of many applications in chemistry; however, the basic principles of light, light-matter interaction, and the operation of spectrophotometers are rarely present in chemistry curricula at the high-school level, or they are only briefly introduced to students before focusing on analytical chemistry applications. In this work, we report the results of a study conducted over several years, aimed to design, optimise, and put into practice a didactic sequence on light phenomena such as reflection, refraction, interference, diffraction, and light dispersion, as well as the basic principles of ultraviolet-visible spectroscopy and spectroscopic instruments. Difficult concepts of light phenomena and related topics were deeply investigated, focusing on the best ways to teach them to high-school students in the framework of the content-specific components identified in the topic-specific pedagogical content knowledge theoretical model. Inquiry-based learning and interactive STEM laboratory activities were combined with a historical epistemological teaching method. Short introductory videos were also recorded to help students during the remote lessons in the COVID-19 pandemic period. In this paper, we report and discuss the research strategy used in order to design and implement the sequence of educational activities, leading to a final optimised didactic sequence that was tested in a pilot study. The main results were obtained from the experimentation with several classes in two high-school technical institutes with a chemistry and material sciences curriculum, along with a group of undergraduate students during the first part of an introductory course on molecular spectroscopy.